From the editors - Esterhuyse, Abel; Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2015)
The role of the military in the making of South Africa1 has always been a contentious issue and has recently again been highlighted when the military was deployed in certain South African neighbourhoods in support of the police to deal with the recent bout of xenophobic violence. During the 2010 Soccer World Cup, the military was deployed to help with border protection and has since been a permanent feature on South Africa’s borders. More recently, the military has also been utilised in counter-poaching operations and the fight against crime inside the country. During the farm labour unrest in the Western Cape in 2012, the provincial government under the national opposition party, the Democratic Alliance, also called on the national government to deploy the military in support of the police in that province. In the more recent past, the Western Cape provincial government also requested military support to deal with gangsterism in certain neighbourhoods of the Western Cape. There seems to be an increasing demand for and an increased deployment of the military in the domestic security realm in South Africa. Domestic military deployments in Africa have always been at the heart of debates about military professionalism and the effect such deployments have on the important relationship between a society and its military. The study of the intimate link between the military and the South African society is the focus of the first article by Lindy Heinecken.